The Potential of San Carlos City, Negros Occidental as Meetings, Incentives, Conventions and Exhibitions Destination - Ramirez, Cybill Ann A.; Mibato, Rizalie N.E. (Philippine Social Science Journal, 2020)
The Meetings, Incentives, Conventions, and Exhibitions (MICE) tourism is a niche segment in the tourism market that has abundant potential and is gaining significance worldwide due to the growth of business tourism. In San Carlos City, the MICE industry is not yet fully developed. The assessment of San Carlos City’s potential as a MICE destination is still necessary to determine if the city has met all the essential requirements. However, the city can accommodate small local events. Hence, the paper assesses the potential of San Carlos City, Negros Occidental as Meetings, Incentives, Conventions, and Exhibitions destination. The paper also determines the stakeholders’ perceived demands of San Carlos City, Negros Occidental as MICE destination in terms of business and trade, educational and scientific, sports and entertainment, and arts and cultural. Furthermore, the paper also determines the challenges and opportunities of San Carlos City as a MICE destination.